Reimagining the intersection of Minangkabau custom and Islam in film Tenggelamnya Kapal Van Der Wijck (2013) / Mastura Muhammad … [et al.] - Muhammad, Mastura; Ismail, Norlela; Azmi, Nur Nafishah; Abu Hassan, Azri (Faculty of Art and Design, 2024)
This paper examines the representation of the Malay muslim world in the Indonesian film Tenggelamnya Kapal van Der Wijck (2013) by using cinematic analysis and a narratological approach. The film intricately explores the interrelationships between Malay culture, focuses on Minangkabau customs and religion while highlighting the significant impacts of strict adherence to these customs within the Malay traditional settings on the love stories of the central characters, Zainuddin and Hayati. In this scholarly exposition, contention revolves around the assertion that the convergence of Malay traditional customs and Islam plays a crucial role and serves as a central premise for overcoming the conflicts and challenges encountered by the central characters in the narrative. Set in the Dutch East Indies during the early 20th century, the film follows the journeys of Zainuddin and Hayati as they navigate the complexities of cultural norms, religious beliefs, and societal expectations. Through textual analysis that emphasises cinematic techniques and a narratological approach, this exploration fosters valuable insights into the dynamics within the specific Malay Muslim community, enriching our comprehension of specific cultural identity and societal complexities. Besides serving as an entertainment outlet, the film unveils dramatic conflicts and social, and religious themes that propagate an insightful representation of the Malay muslim world. It also allows us to explore how cinema shapes and reflects specific cultural representations of the Malay world.